2018
DOI: 10.2147/ott.s176818
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GLUT-1 expression and the PI3K/Akt pathway to enhance the chemosensitivity of laryngeal carcinoma cells in vitro

Abstract: BackgroundThe mechanism of chemoresistance remains unknown. Here, we investigated if glucose transporter-1 (GLUT-1) and PI3K/Akt pathways are associated with the sensitivity to cisplatin in Hep-2 laryngeal carcinoma cells and whether the inhibition of GLUT-1 and the PI3K/Akt pathways enhances the chemosensitivity of Hep-2 cells.MethodThe effects of inhibiting GLUT-1 by a GLUT-1 siRNA, and PI3K/Akt by Ly294002, on cisplatin-induced effects were assessed in vitro.ResultsGLUT-1 siRNA and cisplatin showed a synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…GLUT1 expression was significantly increased after irradiation compared to control cells. These results are similar to those of our previous studies 3‐5,28 and suggest a correlation between elevated GLUT1 expression and radioresistance of LC 5,28,29 . As a well‐known antioxidant, curcumin has both radiosensitizing and radioprotective properties.…”
Section: Discussionsupporting
confidence: 91%
“…GLUT1 expression was significantly increased after irradiation compared to control cells. These results are similar to those of our previous studies 3‐5,28 and suggest a correlation between elevated GLUT1 expression and radioresistance of LC 5,28,29 . As a well‐known antioxidant, curcumin has both radiosensitizing and radioprotective properties.…”
Section: Discussionsupporting
confidence: 91%
“…A dependence on the PI3K/Akt pathway for the expression of pro-inflammatory cytokines, namely IL-6, IL-8, IL-17a, and IL-1β, was also reported by Li et al in synovial fibroblasts isolated from rats with experimental OA ( 77 ). Similarly, in human tumoral cell lines, pharmacological inhibition of the PI3K/Akt pathway was shown to reduce the mRNA expression of Glut-1 ( 78 80 ) as well as the protein levels of HIF-1α and PDK-1 ( 81 ).…”
Section: Discussionmentioning
confidence: 96%
“…Each bar represents the mean ± SEM, n = 5. *p < 0.05; **p < 0.01; ***p < 0.001; ****p < 0.0001. tumoral cell lines, pharmacological inhibition of the PI3K/Akt pathway was shown to reduce the mRNA expression of Glut-1(78)(79)(80) as well as the protein levels of HIF-1α and PDK-1(81).…”
mentioning
confidence: 99%
“…Hypoxia promotes the expression of hypoxia-inducible factor (HIF), which plays an important role in the processes of in ltration, recurrence, and metastasis induced by hypoxia [8][9]. Previous studies also found that the expression of HIF-1α increased and was related to some biological behaviors of laryngeal carcinoma [10][11][12][13]. There have been few reports regarding the relationship between HIF-1α expression and the biological behavior of hypopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%